Subcutaneous Emphysema in a Bantam Fowl - Lokesh, L; Didugu, Mohitha Sree; Rao, J Radhakrishna; Srujan , R (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A 6-month-old male bantam fowl was presented to Veterinary Clinical Complex, Bhoiguda, C.V.Sc., P.V.N.R.T.V.U., Hyderabad with history of anorexia, staggering gait, reduced activity and swelling under the right wing for 2 days. On palpation, the swelling (between right wing and leg) was pale, soft, balloon-like with no pain. It was tentatively diagnosed as subcutaneous emphysema of unknown etiology. On day 1 and 2, a sterile hypodermic needle was used to puncture the skin to extract the accumulated air under aseptic conditions. There was recurrence of emphysema the next day in the same area. On 3rd day after extraction of air, benzathine penicillin was injected into the affected area. There was no recurrence of emphysema thereafter. Benzathine penicillin was injected into the affected area for the next 2 consecutive days. The bird was given B-complex injection for all 5 days. The bird recovered uneventfully without any further complications. Based on the response of bird to the treatment, it was concluded that the case was subcutaneous emphysema of bacterial origin.